Specific cytoarchitectureal changes in hippocampal subareas in daDREAM mice. Issue 1 (December 2016) - Mellström, Britt; Kastanauskaite, Asta; Knafo, Shira; Gonzalez, Paz; Dopazo, Xose; Ruiz-Nuño, Ana; Jefferys, John; Zhuo, Min; Bliss, Tim; Naranjo, Jose; DeFelipe, Javier
Abstract Background Transcriptional repressor DREAM (downstream regulatory element antagonist modulator) is a Ca2+ -binding protein that regulates Ca2+ homeostasis through gene regulation and protein-protein interactions. It has been shown that a dominant active form (daDREAM) is implicated in learning-related synaptic plasticity such as LTP and LTD in the hippocampus. Neuronal spines are reported to play important roles in plasticity and memory. However, the possible role of DREAM in spine plasticity has not been reported. Results Here we show that potentiating DREAM activity, by overexpressing daDREAM, reduced dendritic basal arborization and spine density in CA1 pyramidal neurons and increased spine density in dendrites in dentate gyrus granule cells. These microanatomical changes are accompanied by significant modifications in the expression of specific genes encoding the cytoskeletal proteins Arc, Formin 1 and Gelsolin in daDREAM hippocampus. Conclusions Our results strongly suggest that DREAM plays an important role in structural plasticity in the hippocampus.